La lucha contra la corrupción en la Nueva España según la visión de los neoestoicos - Cárdenas Gutiérrez, Salvador (El Colegio de México, A.C., 2006)
Along with the increasing presence of judicial and administrative officials in New Spain came the development of a courtly culture that entailed corrupt practices such as bribery  and fraud to the public treasury.  Spanish and viceragal authorities  attempted to  deter these  practices through local lawsuits and penal codes. At the same time, many lawyers, moralists and poets censured corruption from the perspective of neo-Stoic philosophy. Topics such as the “deception” produced by vanity and adulation, as opposed  to the “truth” revealed by virtue, were frequent in baroque  sermons,  panegyrics and festive and ceremonial  emblems inspired in this philosophical viewpoint. However, this same viewpoint attempted to unite  ethics and the  struggle  for power by taking advantage of the ludic dimension of virtue, just as Seneca had proposed and the authors  of courtly New-Spanish literature had repeated.